2011
DOI: 10.1007/s11682-011-9124-5
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of motor performance and striatal [18F]fluorodopa uptake in Parkinson’s disease

Abstract: Although [18F]fluoro-L-dopa [FDOPA] positron emission tomography (PET) has been used as a surrogate outcome measure in Parkinson's disease therapeutic trials, this biomarker has not been proven to reflect clinical status longitudinally. We completed a retrospective analysis of relationships between computerized sampling of motor performance, FDOPA PET, and clinical outcome scales, repeated over 4 years, in 26 Parkinson's disease (PD) patients and 11 healthy controls. Mixed effects analyses showed that movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…6). Our observation of severe behavioral effects following injections into anterior/medial regions of the putamen is consistent with several radioligand imaging studies in human subjects showing that measures of symptom progression (e.g., akinesia measured as prolonged reaction times) correlate with the degree of DA loss from medial regions of the striatum, but not with DA loss in the dorsolateral “skeletomotor” region of putamen (Gallagher et al, 2011; Morrish et al, 1996; Pirker, 2003). These results also fit well with the recent finding that injections of bicuculline into the anterior-medial putamen induce hypoactivity in non-human primates (Worbe et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…6). Our observation of severe behavioral effects following injections into anterior/medial regions of the putamen is consistent with several radioligand imaging studies in human subjects showing that measures of symptom progression (e.g., akinesia measured as prolonged reaction times) correlate with the degree of DA loss from medial regions of the striatum, but not with DA loss in the dorsolateral “skeletomotor” region of putamen (Gallagher et al, 2011; Morrish et al, 1996; Pirker, 2003). These results also fit well with the recent finding that injections of bicuculline into the anterior-medial putamen induce hypoactivity in non-human primates (Worbe et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, the largest loss of DA in absolute terms is from the posterior putamen (Ehringer and Hornykiewicz, 1960; Kish et al, 1988) and symptom severity does correlate with the level of putamenal DA depletion (Bernheimer et al, 1973; Morrish et al, 1996; Nandhagopal et al, 2009; Seibyl et al, 1995). Putamenal DA depletion, however, is not a perfect predictor of symptom severity or symptom progression in individual patients (Gallagher et al, 2011; Pavese et al, 2011; Pirker, 2003), suggesting that factors other than putamenal DA influence the genesis of parkinsonian symptoms. Dopamine loss in PD is not restricted to the striatum (reviewed by Rommelfanger and Wichmann, 2010), but has also been observed in the subthalamic nucleus, thalamus, globus pallidus, and cortex (Francois et al, 2000; Freeman et al, 2001; Jan et al, 2000; Scatton et al, 1983; Scatton et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…As in our study, Carli et al [63] required responses into adjacent ports, while the studies that showed MT impairments required movement to more distant ports. Nonhuman primates that have received intraputaminal dopamine antagonist infusions [43] and humans with PD have impairments in both RT and MT, as assessed by a range of tasks under different treatment conditions [8184]. It is therefore unclear whether the apparently inconsistent MT results across studies relate to the specifics of the task structure or the extent of dopamine loss.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study aimed to estimate the predictive value of Unified Parkinson's Disease Rating Scale (UPDRS) and ß-CIT uptake measured by SPECT, on clinical impairment at mean 44 months follow-up [29], showed only a weak correlation between tracer uptake and staging parameters, suggesting a more significant predictive value of UPDRS motor score than b-CIT SPECT. A retrospective analysis of relationships between computerized sampling of motor performance, clinical rating scales, and 18FDOPA PET, over 4 years, revealed that prolonged reaction and movement times were related to lower caudate nucleus 18FDOPA uptake, and abnormalities in hand fine force control were related to mean striatal 18FDOPA uptake [31]. Alternatively, the expression of DAT might be upregulated, also as a compensatory mechanism.…”
Section: Imaging Biomarkersmentioning
confidence: 99%